The value of personal professional monitoring performance data and open disclosure policies in anaesthetic practice: a case report. Issue 4 (1st August 2003) - Bolsin, S; Solly, R; Patrick, A
Abstract : A case is reported in which routine detailed trainee performance monitoring data collected as part of a personal professional monitoring programme were used to help justify to a patient and relatives the unforeseeable nature of a rare complication of a procedure. The data also supported the decision to allow the trainee to undertake the procedure. The personal professional monitoring programme conforms to the highest standards of clinical governance for trainees, consultants, departments, hospitals, and professional colleges. Data from the programme are fed back to the trainees and used to guide training requirements and to provide objective evidence of trainee assessments, practical ability, and competence.